Bioactive agarose carbon‐nanotube composites are capable of manipulating brain–implant interface. Issue 14 (24th December 2013) - Lewitus, Dan Y.; Smith, Karen L.; Landers, John; Neimark, Alexander V.; Kohn, Joachim
ABSTRACT Composite electrodes made of the polysaccharide agarose and carbon nanotubes (A‐CNE) have shown potential to be applied as tissue‐compatible, micro‐electronic devices. In this article, A‐CNEs were functionalized using neuro‐relevant proteins (laminin and alpha‐melanocyte stimulating hormone) and implanted in brain tissue for 1 week (acute response) and 4 weeks (chronic response). Qualitative and quantitative analysis of neuronal and immunological responses revealed significant changes in immunological response to implanted materials depending on the type of biomolecule used. The potential to manipulate tissue response through the use of an anti‐inflammatory protein, alpha‐melanocyte stimulating hormone, was shown in the reduction of astroglia presence near the implant site during the glial scar formation. These results suggest that A‐CNEs, which are soft, flexible, and easily made bioactive, have the ability to modify brain tissue response through surface modification as a function of the biomolecule used. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40297.